Effect of ball feeling training on agility performance in youth football players - Wilfridus Ventus; Mulyono (Mamaos: Journal Physical Education, Sport and Art, 2026)
This study aimed to examine the effect of ball feeling training on agility performance in youth soccer players and to compare the effectiveness of Side Stop and Go and Toe Tap training variations. A quasi-experimental design with a two-group pretest–posttest control group approach was employed. Twenty-one U16 football players were randomly assigned into three groups: Side Stop and Go (n = 7), Toe Tap (n = 7), and Control (n = 7). The intervention was conducted over six weeks with a frequency of three sessions per week. Agility performance was measured using the Illinois Agility Test before and after the training period. Data were analyzed using descriptive statistics and paired sample t-tests with a significance level of p < 0.05. The results showed significant improvements in agility performance in both experimental groups, with the Side Stop and Go group demonstrating the greatest reduction in test time. The control group showed only minimal improvement. These findings indicate that ball feeling training effectively enhances agility performance, particularly when incorporating rapid directional change movements. The study supports the integration of structured ball feeling drills into youth football training programs.